2016
DOI: 10.1002/jcla.22109
|View full text |Cite
|
Sign up to set email alerts
|

The importance of serum biglycan levels as a fibrosis marker in patients with chronic hepatitis B

Abstract: Serum biglycan might be used as a non-invasive marker of liver fibrosis. Further studies are needed to evaluate the usefulness of this marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Most HCCs develop from hepatofibrosis, and the potential curative treatment options are limited (Kimhofer et al, 2015), so it is quite important to look for biomarkers for hepatofibrosis. It has been reported that some substances, such as angiopoietin-like protein 2 or serum biglycan, can be biomarkers for liver fibrosis, but the area under the ROC curve for the reports were lower than 0.9 (Ciftciler et al, 2017;Deng et al, 2017). In this study, the area under the ROC curve for ADHI and ADHII was greater than 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Most HCCs develop from hepatofibrosis, and the potential curative treatment options are limited (Kimhofer et al, 2015), so it is quite important to look for biomarkers for hepatofibrosis. It has been reported that some substances, such as angiopoietin-like protein 2 or serum biglycan, can be biomarkers for liver fibrosis, but the area under the ROC curve for the reports were lower than 0.9 (Ciftciler et al, 2017;Deng et al, 2017). In this study, the area under the ROC curve for ADHI and ADHII was greater than 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Serum biglycan levels have been studied in relation to other diseases, such as hepatitis B and endometrial cancer [41,42], but not in relation to preterm labor. We previously demonstrated that serum biglycan concentrations in early pregnancy are increased prior to presentation with PPROM when compared with those in controls that went on to deliver at term [27].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one study that evaluates BGN as a non-invasive marker for liver fibrosis assessment in human CHB infection,6 but no study about its role in human CHC infection. The BGN level increased significantly in the CHB group when compared with the control group (p<0.001), in agreement with the result of Ciftciler et al ,6 but there is no significant difference in the BGN level between the CHC group when compared with the control group (p<0.96). Liver biopsy was performed to assess the degree of liver fibrosis according to the Ishak scale and classify fibrosis into six stages 19.…”
Section: Discussionmentioning
confidence: 99%